1954
DOI: 10.1111/j.2042-7158.1954.tb11033.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Analgesics: Stereochemical Considerations

Abstract: IN a review article1 in 1952 on "Analgesics," one of the present authors stated "it appears probable from a consideration of the diverse types of compounds which have an analgesic activity equal to, or greater than, that of pethidine, that the minimum requirement for activity may be a hydrophobic group (or collection of groups) containing a basic centre with an overall optimum spatial arrangement." Further "it is possible that the stereochemical configuration of the drug must be complementary to that of a cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
0
2

Year Published

1960
1960
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(115 citation statements)
references
References 20 publications
4
109
0
2
Order By: Relevance
“…Furthermore, the contractions could also be abolished by anoxia or by lowering the temperature to 270 C. Thus it is unlikely that the muscle was being stimulated directly. Beckett & Casy (1954) suggested that morphine-like drugs combined with specific receptors in the central nervous system to elicit an analgesic response. If the action of analgesic drugs on the stimulated ileum is also mediated through a combination with specific receptors, the structural requirements for inhibitory activity should resemble those for analgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the contractions could also be abolished by anoxia or by lowering the temperature to 270 C. Thus it is unlikely that the muscle was being stimulated directly. Beckett & Casy (1954) suggested that morphine-like drugs combined with specific receptors in the central nervous system to elicit an analgesic response. If the action of analgesic drugs on the stimulated ileum is also mediated through a combination with specific receptors, the structural requirements for inhibitory activity should resemble those for analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Analgesic activity resides in only one isomer of pairs of optical enantiomorphs of morphine-like drugs (Beckett & Casy, 1954). The effects of optical stereoisomers of analgesic drugs have been compared on the responses of guinea-pig ileum to electrical stimulation.…”
Section: Stereochemical Considerationsmentioning
confidence: 99%
“…group relative to the piperidine or pyrrolidine rings contradicts the receptor theory of Beckett & Casy (1954).…”
mentioning
confidence: 85%
“…Beckett & Casy (1954) proposed a model based on the assumption that the association of a drug on the receptor site involved three specific subsites: an anionic center to interact with the N atom, a hydrophobic site where the aromatic ring lies and a 'hole' to accommodate C15 and C16. In a recent article we reported the conformational properties of two 16-alkyl analogues of thebaine and oripavine: compounds (III) and (IV) (Fig.…”
Section: Introductionmentioning
confidence: 99%